Genetic dissection of pre‐anthesis sub‐phase durations during the reproductive spike development of wheat. (11th July 2018) - Guo, Zifeng; Chen, Dijun; Röder, Marion S.; Ganal, Martin W.; Schnurbusch, Thorsten
Summary: Flowering time is an important factor affecting grain yield in wheat. In this study, we divided reproductive spike development into eight sub‐phases. These sub‐phases have the potential to be delicately manipulated to increase grain yield. We measured 36 traits with regard to sub‐phase durations, determined three grain yield‐related traits in eight field environments and mapped 15 696 single nucleotide polymorphism (SNP, based on 90k Infinium chip and 35k Affymetrix chip) markers in 210 wheat genotypes. Phenotypic and genetic associations between grain yield traits and sub‐phase durations showed significant consistency (Mantel test; r  =   0.5377, P  <   0.001). The shared quantitative trait loci (QTLs) revealed by the genome‐wide association study suggested a close association between grain yield and sub‐phase duration, which may be attributed to effects on spikelet initiation/spikelet number (double ridge to terminal spikelet stage, DR‐TS) and assimilate accumulation (green anther to anthesis stage, GA‐AN). Moreover, we observed that the photoperiod‐sensitivity allele at the Ppd‐D1 locus on chromosome 2D markedly extended all sub‐phase durations, which may contribute to its positive effects on grain yield traits. The dwarfing allele at the Rht‐D1 (chromosome 4D) locus altered the sub‐phase duration and displayed positive effects on grain yield traits. Data for 30 selected genotypes (from among the original 210 genotypes) in the field displayed a close association with that from the greenhouse. Most importantly, this study demonstrated specific connections to grain yield in narrower time windows (i.e. the eight sub‐phases), rather than the entire stem elongation phase as a whole. Significance Statement: In this study, we divided the reproductive spike development stage into eight sub‐phases in wheat. The Ppd‐D1 (chromosome 2D) and Rht‐D1 (chromosome 4D) loci significantly influenced sub‐phase durations. The most important result is that we demonstrated the connections of narrower time windows (i.e. eight sub‐phases) with grain yield, rather than the long stem elongation phase.